The Effect of High Intensity Acute Re-sistance Exercise with Blood Flow Restriction on Blood lactate and Executive Function - Khalil Pourkhalili; Mahsan Eskandari; Amir Hossein Andalib; Zahra Akbari (Iranian South Medical Journal)
Background: Blood flow restriction (BFR) combined with exercise has gained attention for enhancing the effects of exercise on cognitive function, particularly executive performance. Additionally, lactate, as a metabolic byproduct of exercise, affects the function of the nervous system. The aim of the present study is to examine the effect of acute resistance exercise combined with blood flow restriction on blood lactate changes and executive brain function. Materials and Methods: Fourteen healthy young men aged 18-30 years participated in this study. Each participant attended the laboratory on four separate sessions, with at least 72-hour intervals and randomly assigned to one of the following conditions: control, control with BFR, exercise, and exercise with BFR. Heart rate, arterial blood pressure, and blood lactate levels were measured before and after the interventions. The Stroop test was used to evaluate executive function. Results: Data analysis revealed that lactate, a marker of anaerobic metabolism, significantly increased after exercise and blood flow restriction. However, there were no significant changes in response time to stimuli on the Stroop test after exercise or exercise with BFR. Applying BFR alone in the control group had no significant effect on the Stroop test results. Conclusion: The results show that even though blood lactate levels change, acute resistance exercise, with and without blood flow restriction, is unable to produce significant changes in executive function after exercise.